The driver role of JAK‐STAT signalling in cancer stemness capabilities leading to new therapeutic strategies for therapy‐ and castration‐resistant prostate cancer. Issue 8 (31st July 2022) - Lo, U‐Ging; Chen, Yu‐An; Cen, Junjie; Deng, Su; Luo, Junghang; Zhau, Haiyen; Ho, Lin; Lai, Chih‐Ho; Mu, Ping; Chung, Leland W.K.; Hsieh, Jer‐Tsong
Abstract: Background: Lineage plasticity in prostate cancer (PCa) has emerged as an important mechanism leading to the onset of therapy‐ and castration‐resistant PCa (t‐CRPC), which is closely associated with cancer stem cell (CSC) activity. This study is to identify critical driver(s) with mechanism of action and explore new targeting strategy. Methods: Various PCa cell lines with different genetic manipulations were subjected to in vitro prostasphere assay, cell viability assay and in vivo stemness potential. In addition, bioinformatic analyses such as Ingenuity pathway and Gene Set Enrichment Analysis were carried out to determine clinical relevance. The in vivo anti‐tumour activity of JAK or STAT1 inhibitors was examined in clinically relevant t‐CRPC model. Results: We demonstrated the role of interferon‐related signalling pathway in promoting PCa stemness, which correlated with significant elevation of interferon related DNA damage resistance signature genes in metastatic PCa. Inhibition of JAK‐STAT1 signalling suppresses the in vitro and in vivo CSC capabilities. Mechanistically, IFIT5, a unique downstream effector of JAK‐STAT1 pathway, can facilitate the acquisition of stemness properties in PCa by accelerating the turnover of specific microRNAs (such as miR‐128 and ‐101) that can target several CSC genes (such as BMI1, NANOG, and SOX2). Consistently, knocking down IFIT5 in t‐CRPC cell can significantly reduce in vitro prostasphere formation as well as decrease in vivo tumour initiating capability. Conclusions: This study provides a critical role of STAT1‐IFIT5 in the acquisition of PCSC and highlights clinical translation of JAK or STAT1 inhibitors to prevent the outgrowth of t‐CRPC. Abstract : Activated JAK‐STAT signalling cascade plays a critical role in the onset of therapy‐ and castration‐resistant disease that is associated with stem cell plasticity. IFIT5, a downstream effector of JAK‐STAT signalling pathway, exhibits a new functional role in modulating stemness transcriptional factors (such as BMI1, NANOG and SOX2) by promoting turnover of specific pre‐miRNAs (such as miR‐101 and miR‐128) for these stemness regulators. Specific JAK‐STAT small molecule inhibitors (ruxolitinib and fludarabine) exhibit potent efficacy in therapy‐ and castration‐resistant prostate cancer treatment.